Does digitalization alleviate rural clean energy poverty? - Ying Chen; Ziqi Chen (Asian Development Bank Institute (ADBI), 2024)
This research investigates the impact of digital village development on clean energy poverty (CEP) in rural areas within the context of energy and digitalization transition in the People's Republic of China (PRC). Utilizing the Index of Digital Rural County (IDRC) and China Family Panel Studies (CFPS) statistical data from 2020, our findings suggest that the establishment of digital villages has a positive effect on alleviating CEP in rural households. Furthermore, our analysis reveals the mechanisms through which this occurs, including the enhancement of wealth and the acceleration of awareness transformation among rural households. Even when accounting for the influence of peers, the alleviating effect of digital villages on rural household CEP remains evident. Heterogeneity analyses demonstrate that households with younger members, higher levels of education, digital access, and those located in central areas experience greater benefits from digital dividends. Subindex analyses indicate that digital governance plays a particularly critical role in mitigating rural household CEP. Lastly, our results offer policy implications for other developing nations seeking to address CEP through digitalization.
Keywords: Q56; R11; 330; digital village; rural household CEP; wealth; awareness; ordered probit model